Orange juice sensory with different sugars - Back, Patrícia Inês Kemper; Steinhaus, Jocieli; Ramires, Maiara Figueiredo; Stoll, Douglas; Vasconcelos, Márlon de Castro; Weber, Fernanda Hart (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
Brazil is the world’s largest producer and exporter of orange juice. Orange juice is a complex product, formed by an aqueous "blend" of various volatile and unstable organic components, responsible for its taste and aroma, as well as sugars, acids, minerals, vitamins and pigments. However, due to the more acidic flavor characteristic of orange juice, many consumers use the use of "common" crystal sugar for their consumption, which may reduce the nutritional quality of the final product. Thus, the objective was to evaluate the acceptance of orange juice sweetened with brown sugar, honey, and refined sugar, by assessing the sensory perception of consumers. The work was developed at the State University of Rio Grande do Sul. The oranges of the Valencia variety, after selection, washing and sanitization were submitted to the juice extraction process manually, and after filtration, 4.5 liters of orange juice were collected. They were then separated into three 1.5 liter portions in three 2 liter containers each, and diluted with the addition of 0.5 liters of water and “ordinary” crystal sugar, brown sugar and honey to 14 ° Brix. The acceptance test was performed by a team of 31 untrained judges, and the orange juice was evaluated for its appearance, taste, acidity, sweetness and overall impression, using a structured hedonic scale evaluation form. Nine points. Orange juice sweetened with refined sugar was presented as the best option of the evaluators, presenting higher grades in all tested attributes.